BEHAVIOR ON THE STAGE (Web of Technology: Multidimensional Research Journal, 2025)
This article discusses the fact that movement is the basis of stage art. Recommendations are given regarding stage movement. K.S. Stanislavsky's definitions of movement are cited as examples to prove the idea.